EXAMINATION METHOD OF THE EFFECT OF THE INCIDENCE ANGLE OF LASER BEAM ON DISTANCE MEASUREMENT ACCURACY TO SURFACES WITH DIFFERENT COLOUR AND ROUGHNESS - Daliga, Karol; Kurałowicz, Zygmunt (Boletim de Ciências Geodésicas, 2016)
Interest in the influence of the incidence angle of a laser beam to distance measurements can be seen in many areas of science and technology: geodesy, glaciology, archaeology, machine automation, and others. This paper presents results of measurements of the effect of the incidence angle of a laser beam to distance measurements to the surfaces of different colour and roughness by Topcon’s electro-optical total station with an accuracy of 3 mm. Measurement method and the method of elimination of test stand errors are presented. The results of measurements have been analysed and the influence of selected factors (surface colour and roughness, lack of instrument rectification) on the distance measurement have been discussed. It is also shown the critical incidence angle above which it can be impossible to measure distances to reflective foil with tested total station.